THE IMPORTANCE OF LEARNING FOREIGN LANGUAGE - Omonova Sugʻdiyona Muqimjonovna; Xamidov Nodirbek (TADQIQOTLAR, 2025)
Abstract:In today’s rapidly globalizing world, the ability to speak foreign languages has become a crucial skill for both personal and professional success. This article explores the diverse benefits of learning foreign languages, including improved career prospects, enhanced cultural understanding, cognitive development, better travel experiences, and personal growth. Drawing on recent studies and real-world examples, it emphasizes why multilingualism is more important now than ever before. The paper also discusses effective language learning strategies and encourages individuals